Model of pareto-efficient relationship of market counterparty viewpoint of inkrementalism concept as the basis of harmonize its goals and interests - Варцаба, В. І.; Петренко, В. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article, the existence of a direct connection between the fact of reaching a pareto-optimal market state by any system as a consequence of achieving and sustaining harmonized relationships between all of its sharers, is proved on the basis of the analysis of theoretical principles, definitions, categories, patterns and characteristics of welfare economics and the conception of social prosperity. Identified condition of effective interaction of individuals or groups based on their ability and willingness to harmonize their own and others' interests with a balance of interests and benefits. Demonstrated the feasibility of using the theory inkrementalizmu for improvement and harmonization of processes of interaction of agents market through the implementation of the necessary management of intellectual capital of a part of their human resources as intellectual elite.